Playing real : mimesis, media, and mischief - Hunter, Lindsay Brandon (Northwestern University Press, 2021)
"Playing Real: Mimesis, Media, and Mischief explores the integration and interaction of mimetic theatricality and representational media in twentieth- and twenty-first-century performance. It focuses on performances that force confrontation between notions of authenticity and artifice"--